Development of pyruvate oxidase-based amperometric biosensor for pyruvate determination - Knyzhnykova, D.V.; Topolnikova, Ya.V.; Kucherenko, I.S.; Soldatkin, O.O. (Вiopolymers and Cell, 2018)
Aim. The development and optimization of the amperometric biosensor for pyruvate determina-tion. Methods. Immobilized pyruvate oxidase was used as a biorecognition element of the biosen-sor, a platinum disc electrode- as an electrochemical transducer. Results. Different variants of immobilization of pyruvate oxidase were tested and the optimal one was chosen for the creation of a biorecognition element of the biosensor. Optimal concentrations of cofactors for the best per-formance of the pyruvate oxidase-based biosensor were selected. The developed biosensor dem-onstrated a high sensitivity to pyruvate and wide linear range of work. High selectivity of the pro-posed biosensor towards electrically active substances and other substrates present in real samples was shown. The biosensor is characterized by high signal reproducibility and operational stability over two weeks. Conclusions. The highly selective amperometric biosensor for determination of pyruvate in biological samples has been developed. Its analytical characteristics are studied. The biosensor can be further used for the pyruvate analysis in blood serum.